The association of economic and cultural capital with the NEET rate: differential geographical and temporal patterns - Enrico Ripamonti; Stefano Barberis (Journal for Labour Market Research, 2021)
Using data from 103 Italian provinces, we investigated the relationship between local/regional development, and NEET. We constructed an indicator of cultural capital and another of economic capital and we studied their relation with the NEET rate. Covariance Structure Analysis with Generalized Least Squares estimation was employed, considering a three time-points retrospective model. Results indicate a consistent protective effect of the economic capital on the NEET rate, both in the short run (2 years) and in the medium run (10 years). However, this effect has been obtained in the Central provinces (at 2 and 10 years) and Southern provinces (at 10 years), but not in the Northern provinces. A mediation analysis indicated that, historically, the cultural capital may partly mediate the effect of the economic capital. We did not detect a significant direct effect of the cultural capital on the NEET rate, which is strongly mediated by the action of the economic capital. Together, these results denote that the economic capital is a strong predictor of NEET, but not in very competitive economic areas.
Keywords: 330; Cultural capital; Economic capital; NEET; School dropout; Southern European welfare